2018
DOI: 10.3390/ma11020266
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of the Heat-Affected Zone Mechanical Properties on the Behaviour of the Welding in Transverse Plate-to-Tube Joints

Abstract: Eurocode 3 establishes the component method to analytically characterize the structural joints between beam and columns. When one of the members involved in the joint is a hollow section (i.e., a tube) there is a lack of information for the specific components present in the joint. There are two different ways to bridge the gap: experimental testing on the actual beam column joints involving tubular sections; or numerical modelization, typically by means of finite element analysis. For this second option, it i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…For weld modeling, the same material properties as those of the corresponding welded brace member were adopted. Some previous research [24,38] carried out in similar situations has confirmed that differences when the base material properties of the steel are also used to model the welds are not noticeable. Although some gaps were smaller than those in EN-1993-1-8 [4], the tests were carried out prior to the formulation of the code, and they were used in this research only for validation of the numerical model.…”
Section: Validation Of Finite Element Modelingmentioning
confidence: 76%
See 2 more Smart Citations
“…For weld modeling, the same material properties as those of the corresponding welded brace member were adopted. Some previous research [24,38] carried out in similar situations has confirmed that differences when the base material properties of the steel are also used to model the welds are not noticeable. Although some gaps were smaller than those in EN-1993-1-8 [4], the tests were carried out prior to the formulation of the code, and they were used in this research only for validation of the numerical model.…”
Section: Validation Of Finite Element Modelingmentioning
confidence: 76%
“…Although pre-galvanizing countermeasures should be considered to avoid cases of brittle cracking resulting from hot-dip galvanizing on cold-formed tubes [21,22], when the process is carried out correctly, this embrittlement effect has been found to be negligible, even in hot-dip galvanized welded joints submitted to fatigue loads [23]. Together with all the previous statements, we can assume that the heat-affected zone (HAZ) in structural steel, and particularly in HSS, does not affect the welded joint behavior [24].…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…Scholars divide the vicinity of weld into weld seam, overheated zone, normalized zone, partial normalized zone and grain refined zone in detail. 35 Because the mechanical properties of the weld material are better than those of the base material, using the fatigue coefficient of the base material instead of the weld material coefficient can obtain a safer design criterion. Moreover, the decrease of mechanical properties in heat affected zone is caused by the increase of austenite and the coarsening of grain, so it can be regarded as the increase of initial defect distribution.…”
Section: Methodsmentioning
confidence: 99%
“…(2) For welds, comments regarding the mechanical properties in the heat-affected zone [23] where considered. The nominal yield limit and ultimate strength values provided by the electrode manufacturer were used, being f y =500 MPa and f u =570 MPa respectively.…”
Section: Numerical Modellingmentioning
confidence: 99%